Women’s Dual Roles In Barru Districk - Mario Mario; Idham Irwansyah Idrus; Riri Amandaria; Mauliadi Ramli (Pinisi Journal of Social Science, 2023)
The purpose of this study was to find out what factors encourage women to choose the profession as cleaning workers and how the time allocation for women who serve as cleaning workers in Barru District, Barru Regency. This research is descriptive qualitative. From this research data in the form of primary data collected directly on the object. As for the data in the form of secondary data obtained from the Office of Housing and the area. Data collection techniques were carried out by interview, observation, and documentation techniques. The sample informants in this study were 11 people. Data collection was carried out using a purposive sampling technique, with the characteristics of the informants, namely women cleaning workers, women from Barru District, women who are already married and women who have children. The results of this study indicate that there are 4 factors that encourage women to choose the profession as cleaners, namely (1) economic factors, the large amount of costs or basic needs in the family causes women to leave their domestic sphere to the public sphere, namely by working. (2) environmental factors, some of them work as female cleaners due to invitations from their closest friends, (3) individual factors, they work of their own free will, and (4) . Low education causes a person's ability to be very limited. Working as a janitor does not necessarily have to be highly educated. while the allocation of time for women cleaning workers is divided into 2 types, namely before going to work, cleaning up homework and the second time, namely going straight to work.